2016
DOI: 10.3727/152599516x14610017108747
|View full text |Cite
|
Sign up to set email alerts
|

The Spirit Lives on: The Legacy of Volunteering at the Sydney 2000 Olympic Games

Abstract: This study examines the volunteer legacy of a mega-sport event. An online, qualitative, open-ended questionnaire (n = 15) and in-depth interviews (n = 10) were administered to and conducted with Sydney 2000 Olympic volunteers to ascertain the legacies that exist at least 10 years after the completion of the event. The results show that the legacy of the Olympic volunteer experience includes the starting and/or rekindling of a volunteer career, the development of a unique set of skills and abilities, and nosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…In other words, the volunteer tourism generated was not related to any active event leverage strategy. Similarly, Fairley et al (2016) found that an organic volunteer legacy existed 10 years after the 2000 Sydney Olympic Games. They found that as a result of volunteering at the Olympics volunteers started or rekindled a volunteer career, developed a unique set of skills and abilities, and generated nostalgia for the atmosphere of the Games.…”
Section: Engaging Volunteers From Regional Communities 435mentioning
confidence: 95%
See 1 more Smart Citation
“…In other words, the volunteer tourism generated was not related to any active event leverage strategy. Similarly, Fairley et al (2016) found that an organic volunteer legacy existed 10 years after the 2000 Sydney Olympic Games. They found that as a result of volunteering at the Olympics volunteers started or rekindled a volunteer career, developed a unique set of skills and abilities, and generated nostalgia for the atmosphere of the Games.…”
Section: Engaging Volunteers From Regional Communities 435mentioning
confidence: 95%
“…Larger and more unique events attract more diverse volunteer profiles (Chalip, 2000;MacAloon, 2000) and also attempt to recruit and retain a substantial number of volunteers from the resident population (Cuskelly et al, 2006). Research has suggested the benefits of cultivating a volunteer base in a community may last long after the event and assist in building event and tourism volunteer resources in the future (Fairley, Gardiner, & Filo, 2016;Fairley, Green, O'Brien, & Chalip, 2015;Ralston, Lumsdon, & Downward, 2005). Thus, leaving a legacy of volunteering in a community may be a stated outcome of the event organizers (Doherty, 2009;Downward & Ralston, 2006;Fairley et al, 2016).…”
Section: Engaging Volunteers From Regional Communities 435mentioning
confidence: 99%
“…Similarly, skill development leading to the enhancement of an individual's future career opportunities was a key expectation (Barron & Rihova, 2011;Clary, Snyder, & Ridge, 1992;Elstad, 1996). Previous research has often considered knowledge development and acquisition of skills as one factor (Clary et al, 1992;Clary et al, 1998;Elstad, 1996;Fairley, Gardiner, & Filo, 2016). However, these findings indicate that knowledge acquisition and skill development are in fact two distinct expectations that contribute to the overall experience.…”
Section: Discussionmentioning
confidence: 99%
“…Event Management has published a growing number of articles related to events and cities. For example, there have been a number of recent studies considering the effects of the Olympic Games in different cities (Emery, Kerr, & Crabtree, 2016;Fairley, Gardiner, & Filo, 2016;Potwarka, Tepylo, Fortune, & Mair, 2016). Other events such as the ECOC have also been analyzed in their urban context (Vareiro, Santos, Remoaldo, & Ribeiro, 2016).…”
mentioning
confidence: 99%